ESENSI PEMBINAAN KARAKTER ANAK BAGI ORANG TUA DAN GURU - Andi Saputra Dasopang; Nur Khomisah Pohan; Zulkifli Lessy (DIRASATUL IBTIDAIYAH, 2022)
A child's good character doesn't just come overnight; it is developed over time through education. One of the character education strategies for the younger generation is to include early religious education. Children's character can be formed from an early age to become a strong, independent, and responsible person. Parents undoubtedly play an important role in ensuring that children grow and thrive in an environment that fosters their character growth. The development of a good child's character does not happen overnight or without the help of schools. Starting religious education from an early age is one of the character building strategies for children. From an early age, children's character can be developed into a good, tough, independent, and responsible person. Of course, parents are very important in ensuring that children grow and thrive in an environment that encourages character development. Parents are role models for their children, therefore it is important for them to be able to set an example. The purpose of this essay is to investigate the relationship between child psychology and the Islamic approach to character education. The author concludes that character education in children is interpreted similarly by Islam and psychology. This study draws on reviews of published books and journals, which are the basis for this article.